META-ANALYSIS ON ENTREPRENEURIAL SKILLS FOR INTEGRATION IN RADIO, TELEVISION, AND ELECTRONIC WORK PROGRAMME (Proceedings of the International Conference on Future of Education, 2025)
Enterprise skills required for self-reliance and wealth creation are crucial for survival in any nation. The gap between the enterprise skill needs and Radio, Television, and Electronic Work (RTEW) students’ skills exists due to insufficient curriculum adopted in technical colleges. Although entrepreneurial skills are discovered effective but have not been implemented in RTEW trade curriculum in Nigeria. This has led to RTEW students graduating from Nigerian technical colleges without the needed enterprise skills that will effectively equip them for the world of work. Hence, there is need to investigate entrepreneurial skills suitable for inclusion into RTEW trade curriculum to trim the problem of skills shortages among RTEW students at technical colleges levels. As such, meta-analysis of entrepreneurial skills was conducted with the purpose of sieving desired entrepreneurial skills needed for integration into the curriculum of Radio, Television and Electronics Work trade in Nigerian technical colleges. The research design of the study is meta-analysis. The methodology in meta-analysis involved development of research question; forming criteria; search strategy including data bases and manual searching; protocol registration; title, abstract, and full text screening; extracting and checking data; quality assessment of data; statistical analysis; and manuscript writing.    The sample of the study were 10 different scholarly articles. The rational for selecting 10 studies was that they were meaningfully pooled and their results were sufficiently similar. In addition, similar degree of evidences was provided by the 10 studies chosen. The Scope of the study was limited to databases such Science Direct and JSTOR, though local conferences conducted in Nigeria were also consulted for data gathering. Descriptive statistics is employed for analysis of data gathered from the present study. However, it was discovered that the results of the meta-analysis of literature conducted revealed that the main focus of this research was on enterprise skills that included entrepreneurial awareness, qualities of entrepreneurs, self and paid employment, ethics in life and business, business ideas and opportunities, starting and operating a business, and business plans, among others. Thus, enterprise skills were needed in the Radio, Television, and Electronic Work trade curriculum due to their focus on identification of various opportunities which help develop and implement business concepts. In the context of the present study, discoveries are synonymous with the findings of the study. Therefore, the discoveries in this study are regarded as results which are recommended for inclusion in future curriculum review of RTEW trade in technical colleges of Nigeria. Importantly, the implication of the results is to overcome potential challenges encountered in the job market and guide for effective curriculum design in Radio, Television, and Electronic Programme in order to help students in developing the necessary skills needed for successful employment after graduation so that they could contribute to the sustainable development of Nigeria.
Keywords: Aptitudes, competencies, enterprise, infusion, vocation